Analisis Pengelolaan Anggaran Pendapatan Belanja Desa (APBD) di Desa Lemito Kecamatan Lemito Kabupaten Pohuwato - Edy Sijaya (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2025)
The objectives of the research to be conducted are as follows: To determine the Management of Village Revenue and Expenditure Budgets The method in this research is descriptive analysis with a quantitative and qualitative approach, namely research that uses numbers and words or sentences and images using samples and using questionnaires as a primary data collection tool. The population in this study is the village head of Lemito and village officials totaling 20 people, BPD 5 people, and community leaders of Lemito village, Lemito sub-district, Pohuwato Regency totaling 15 people. So the population in this study is 40 people. The sampling technique in this study uses Purposive Sampling, namely a method of sampling with certain considerations that clearly know the focus of the problems raised in this study. So the sample in this study is the village apparatus of Lemito totaling 20 people, BPD 5 people plus the Lemito village community that the researcher determined based on considerations, namely 15 people. So the total sample used as respondents is 40 people. The results of the study indicate that the four management indicators, namely planning, organizing, mobilizing, and monitoring in the management of the Village Budget (APBDes) in Lemito Village, Lemito District, have basically been running well, although of the four indicators that received a very good or very high rating was the planning indicator. Meanwhile, those that received a low or good rating and need to be improved by the Lemito village government in managing the APBDes were the organizing and mobilizing indicators, which still lack community participation or community involvement in the implementation of activities sourced from the APBDes in Lemito Village. Meanwhile, the results of the study on the APBDes seen from the indicators of Revenue, Expenditure, and Financing, based on respondents' assessments that for the 2019 budget year, the Lemito Village APBDes of1,947,351,497.00 was considered insufficient for village needs, especially in terms of financing development and community empowerment. The researcher's findings indicate that the amount of the APBDes is still largely used for employee expenses, including payments for village officials' salaries, BPD salaries, incentives, and others.